Investigating cryptocurrencies understanding, extracting, and analyzing blockchain evidence - Furneaux, Nick (Wiley, 2018)
Bitcoin has traditionally been the payment system of choice for a criminal trading on the Dark Web, and now many other blockchain cryptocurrencies are entering the mainstream as traders are accepting them from low-end investors putting their money into the market. Worse still, the blockchain can even be used to hide information and covert messaging, unknown to most investigators.